The Effect of Administration of Cow Stage and NPK Fertilizer on The Growth and Results of Chrysan Plants (Chrysantthemum morifolium, R.) - Febriyani Edilia ndarung; I Gusti Bagus Udayana; I Gusti Made Arjana (GEMA AGRO, 2023)
Chrysanthemum (chrysanthemum morifolium R.), is an ornamental plant that has economic value and has the potential to be developed in national and international trade. This study aims to determine the effect of the type of cow manure and NPK fertilizer dosage on growth and yield of chrysanthemum plants. The hypothesis put forward in this study was that cow manure (20 tons ha-1) and NPK fertilizer doses (1000 kg/ha) could increase growth and yield of chrysanthemum plants. The experimental design used in this study was a factorial randomized block design with 2 treatments, namely the type of organic cow manure (S) consisting of 4 levels, namely: S0 = without cow manure, S1 = 10 ton/ha-1 cow manure, S2 = 20 tons/ha-1 cow manure, S3 = 30 tons/ha-1 cow manure, and the dosage of NPK fertilizer consists of 4 levels, namely: D0= without NPK fertilizer, D1= 1000 kg/ha, D2= 2000 kg/ha, D3 = 3000 kg/ha. Research data were analyzed statistically using analysis of variance. For a single treatment that had a significant to very significant effect, it was continued with the LSD test at the 5% level. The results of statistical analysis showed that the interaction between the type of cow manure and the dose of NPK fertilizer (S x D) had no significant effect on (Pâ‰¥0.05) on all observed variables. The highest economic fresh weight of flowers was obtained at the type of manure 20 tons/ha, namely 26.53 g, compared to no organic fertilizer, namely 23.55 g. The highest economic fresh weight of flowers was at a dose of NPK 1000 kg/ha (D1), namely: 26.26 g, compared to NPK 2000 kg/ha is 24.98 g.